Dampak Media Sosial terhadap Minat Wirausaha Mahasiswa di Usia Muda - Imran Hutabarat; Nadia Azzahra; Putri Azhra Sitepu (Income Journal: Accounting, Management and Economic Research, 2024)
This study aims to determine and analyse the influence of social media on students' business interest at a young age. This study uses primary data, namely data obtained from surveys conducted through questionnaires distributed to respondents. Respondents in this study were 40 people. The results of the respondents' answers from the questionnaire were then tested using SPSS software, then the results showed that H0 was accepted, which means that there is an influence of social media on students' business interest at a young age. In more detail, social media has an effect of 75.7% on students' business interest at a young age.